Arbitrary amplitude solitary waves in plasmas with dust grains of opposite polarity and non-thermal ions - Maharaj, S.K.; Bharuthram, R.; Singh, S.V.; Pillay, S. R.; Lakhina, G. S. (My University, 2010)
The existence of large amplitude solitary waves in a plasma comprised of a cold negative dust fluid, adiabatic positive dust fluid, Boltzmann electrons and non-thermal ions is theoretically investigated. Different regions in parameter space that correspond to different values of the ratio of the charge-to-mass ratios of the positive and negative dust grains have been identified where either negative or positive potential solitary wave structures occur and a region where coexistence of negative and positive potential solitary waves is supported.
Keywords: Solitary waves in plasma; Boltzmann electrons; Non-thermal ions